PKM PENERAPAN MANAJEMEN REKAM MEDIS SESUAI DENGAN LEGALITAS PADA FISIOTERAPI MANDIRI DI KOTA SEMARANG - kuswardani -; Sigit Sugiharto; Dwi Nur Astuti (Jurnal Implementasi Pengabdian Masyarakat Kesehatan (JIPMK), 2021)
ABSTRACTThe activity of this society is an effort to increase in knowledge, keterampilah as well as the managing understanding of the Indonesian profession's Physiotherapist at improving the ability to manually recording medical records or electronically appropriate Permenkes numbers 269-year-old 2008 concerning the Medical Records. The special target of PKM's activity is teaching the assistance system on independent physiotherapy that is the IFI branch member of the Semarang to increase skills in creating manual medical records or electronics that suit the legality legality in Indonesia. he method of devotion is carried out by providing assistance from giving extension and discussion, manual medical record-making training, electronic medical record-making training, trials, revisions, and submission medical records from participants. The method of devotion is carried out by providing assistance from giving extension and discussion, manual medical record-making training, electronic medical record-making training, trials, revisions, and submission medical records from participants. The PKM program activities were implemented with the extension and training method over online in the manner) Pre-squad survey, b) Preparation of tools and training materials, c) Preparation pelatiahan's method, d) Training Board and Independent PHYSIOTHERAPIST,) F physiotherapist, G-making and Report. Based on the results of training obtained their significant results so they can create a medical record that they originally ignored the documentation.Said Iinch: Assistance, IFI, the independent physiotherapy, medical record